VISUALISASI MELALUI PENDEKATAN METAFORA PADA POSTER NORTH meet SOUTH = UNITY - Eston Kamelang Mauleti (Jurnal Da Moda, 2021)
Poster is a two-dimensional visual media with large format that is useful for conveying commercial, social, cultural, political messages. Large format is used to display messages through images. Images on a poster are generally large and have a strong appeal so that it can attract the attention of the public immediately see it. The development of posters began in the late 17th century until now. European countries have an excellent poster tradition. Germany is one of them, the growth of posters in the country became part of the life of its modern society. Many moral and social messages that inspire reason are delivered routinely. Plaque-Sozial e.V. und vom Bund Mitteldeutscher Grafdesigner or social poster association and graphic designer Germany regularly holds competitions and exhibitions on an international scale. In the middle of 2016, a competition and exhibition was held for the third time with the theme "Vision". Participants consisted of artists and poster designers from all over the world. Poster works by the author were also selected by the jury and exhibited at The Association of German Museums for Galvanotechnik e. V. Leipzig, Germany takes place from August 13-25, 2016. The author displays poster visualization through a metaphorical approach. Key words : poster, visual metaphor